(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Diabetes mellitus (DM) is a chronic disease with a steadily increasing prevalence worldwide and carries the risk of serious complications, one of which is diabetic foot ulcer (DFU). Preventing such complications requires adequate education and strong assessment skills, particularly at the community level. This community engagement program aimed to improve the skills of health cadres and patients in using a web-based application to determine DFU risk levels. The methods involved target group survey, preparation of materials, training sessions including socialization and demonstration of diabetic foot care protocols, and pre- and post-training evaluation. Most participants were aged 56–65 years (50%), female (75%), and had lived with DM for more than five years (70%). The mean skill score increased from 68.5 (pre-test) to 86.7 (post-test), with an N-Gain of 57.8% (moderate category). In conclusion, the web-based application was moderately effective in improving DFU risk assessment skills, although continuous support and the use of simple educational media are still needed, especially for older participants.